Hypercalcemia as the first manifestation of childhood acute lymphoblastic leukemia: a case report - Pan Liangwu, Zhu Wenting, Chen Cheng, Chen Riling (Xin yixue, 2023)
Acute lymphoblastic leukemia （ALL） is a malignant tumor with the highest incidence during childhood. ALL is mainly characterized with fever， pale face， fatigue and bleeding， etc.， which is primarily involved with the liver， spleen， lymph nodes and mediastinum. Here， we reported a 5-year-old boy diagnosed with ALL and he was admitted due to intermittent vomiting. He presented with hypercalcemia as the first manifestation. Physical examination showed no liver， spleen and lymph node enlargement. Peripheral blood test revealed no significant changes in the classification of white blood cells. Finally， the diagnosis of ALL was confirmed by bone marrow cell morphological examination and flow cytometry. This case of ALL with hypercalcemia as the first presentation is rare in clinical practice， providing reference for clinical diagnosis and treatment.